ANALISIS KOMPARASI KUALITAS INFORMASI AKUNTANSI SEBELUM DAN SESUDAH PENGADOPSIAN PENUH IFRS DI INDONESIA - Glory Augusta E.M. Sianipar; Marsono Marsono (Diponegoro Journal of Accounting, 2013)
This study aims to test whether there is any difference between before and after the fulladoption of IFRS on the financial statements of companies listed on the Stock Exchange, with aconsideration of the impact on the quality of accounting. This study uses earnings management,relevance and value of timely loss recognition to assess the quality of accounting information.This research is an empirical study with purposive sampling techniques in data collection.Data obtained from secondary data manufacturing company's financial statements during theyears 2011 through 2012. This research analyzed using Paired-Sample T Test and Chow Test.Results of this study indicate that there were no difference between before and after the fulladoption of IFRS on the value relevance, timely loss recognition, and earnings management.